Preparation method of electrolyte simultaneously applicable to acidic, near-neutral and alkaline zinc-based energy storage devices

By introducing sodium 2,6 naphthalene disulfonate into the electrolyte of aqueous zinc metal batteries, the solvation structure of zinc ions and the construction of a single molecule layer is solved, and the stability and electrochemical performance of zinc anode in a wide pH range is solved. Problem, the cycle life and electrochemical performance of zinc-based energy storage devices have been significantly improved.

CN119297437AActive Publication Date: 2025-01-10FUJIAN NORMAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411642940.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-10
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The thermodynamic instability and electrochemical performance of the zinc negative electrode in a water-based zinc metal battery in a wide pH range leads to a reduced circulation performance and lacks additive-regulating electrode interface and solvation structure adapted to acidic, near-neutral and alkaline electrolytes.

Method used

Introduce sodium 2,6 naphthalene disulfonate additives into acidic, near-neutral and alkaline electrolytes to regulate the solvation structure of zinc ions, accelerate the desolvation process, and build an ordered single-molecule layer to isolate water through chemical adsorption Contact with the electrode to slow down side reactions.

Benefits of technology

It improves the thermodynamic stability and electrochemical reversibility of zinc negative electrodes, extends the cycle life of zinc-based energy storage devices, and significantly improves the electrochemical performance under wide pH conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297437A_ABST
    Figure CN119297437A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an electrolyte simultaneously suitable for acidic, nearly neutral and alkaline zinc-based energy storage devices, and belongs to the technical field of aqueous zinc metal secondary batteries. According to the invention, sodium 2, 6-naphthalene disulfonate (26-NADS) is used as an additive to be respectively introduced into an acidic electrolyte, a near-neutral electrolyte and an alkaline electrolyte. 26-NADS regulates and controls the solvation process of Zn < 2 + > through sulfonic acid groups at the two ends, a molecular layer can be formed on the surface of the electrode, concentration polarization of zinc ions in an acid / near-neutral electrolyte is delayed, deposition kinetics of the zinc ions is accelerated, meanwhile, local oversaturation of [Zn (OH) 4] < 2-> in an alkaline electrolyte is inhibited, and the electrochemical performance of the electrode is improved. And finally, dendritic crystals and side reactions of the zinc negative electrode in the wide-pH electrolyte are inhibited. Besides, the acidic / nearly neutral ZnMnO2 total battery circulates for 13000 circles under the current density of 5 A g <-1 > and circulates for 5000 circles under the current density of 3 A g <-1 >, and the alkaline ZnNi0. 8Co0. 1Mn0. 1O2 total battery circulates for 500 circles under the current density of 3 A g <-1 >. The preparation process is simple, the effect is remarkable, the cost is low, and the requirements of environmental economic benefits are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aqueous zinc metal secondary batteries, and in particular to a method for preparing an electrolyte suitable for acidic, near-neutral and alkaline zinc-based energy storage devices and applications. Background Art

[0002] Aqueous zinc metal batteries have abundant resources and large volumetric capacity (5855 mAh cm -3 ) and a suitable redox potential (-0.76 V vs standard hydrogen potential) have aroused a research boom. However, the practical application of aqueous zinc metal batteries still faces challenges such as side reactions related to water and dendrite growth. In aqueous electrolytes, due to the high polarity and small radius of water molecules, water molecules and zinc ions coordinate to form a highly directional and ordered solvation structure. During the desolvation process, the active water molecules present in the solvation structure will decompose into H near the zinc negative electrode. + and OH - , hydrogen evolution reaction occurs, and the generated hydrogen gas causes the battery to swell, causing safety problems, and also reduces the coulombic efficiency of the battery. Therefore, water molecules aggravate the thermodynamic instability of the zinc negative electrode, resulting in reduced cycle performance. In addition, aqueous electrolytes, as one of the important components of batteries, are mainly divided into acidic electrolytes, near-neutral electrolytes and alkaline electrolytes according to pH value. Therefore, enhancing the stability of the zinc negative electrode is crucial to improving the electrochemical performance of aqueous zinc metal batteries in wide pH aqueous electrolytes.

[0003] The strategy of introducing organic additives into the electrolyte can modify the zinc ion solvation process and the electrode / electrolyte interface at the same time, and has the advantages of simple operation and significant effect. However, recent research reports on zinc metal battery additive modification are limited to single acidic and alkaline electrolytes, lacking additives that can adapt to acidic, near-neutral and alkaline wide pH electrolytes. Therefore, it is urgent to explore additives to regulate the electrode interface and solvation structure, and improve the stability and electrochemical reaction kinetics of zinc negative electrodes in a wide pH range.

[0004] The invention introduces 2,6-naphthalene disulfonate sodium additive into acidic, near-neutral and alkaline electrolytes to obtain a wide pH electrolyte, thereby improving the thermodynamic stability of the zinc negative electrode under wide pH conditions. On the one hand, 2,6-naphthalene disulfonate sodium adjusts the solvation structure of zinc ions, accelerates the desolvation process, and alleviates the concentration polarization at the electrode interface through the double capture function, thereby inhibiting the growth of dendrites; on the other hand, 2,6-naphthalene disulfonate sodium self-assembles through chemical adsorption to form a molecular layer, isolates the contact between water and the electrode, slows down the side reaction, and improves the reversibility of the deposition / stripping of the zinc negative electrode. Summary of the invention

[0005] The purpose of the present invention is to provide an electrolyte preparation method and application that is simultaneously applicable to acidic, near-neutral and alkaline zinc-based energy storage devices. By introducing sodium 2,6-naphthalene disulfonate additives into acidic, near-neutral and alkaline electrolytes, the solvation structure of zinc ions is reconstructed, the desolvation process is accelerated, and an orderly and stable monolayer is constructed by chemical adsorption to protect the zinc negative electrode, thereby improving the electrochemical reversibility of the zinc-based energy storage device.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention discloses a method for preparing an electrolyte that is applicable to acidic, near-neutral and alkaline zinc-based energy storage devices, and the preparation steps are as follows:

[0008] (1) dissolving a soluble acidic salt in deionized water to prepare an acidic salt solution, wherein the concentration of the acidic salt solution is 2-5 mol L -1 , adding a certain amount of sodium 2,6-naphthalene disulfonate to prepare an acidic electrolyte, wherein the pH range of the acidic electrolyte is 1-4;

[0009] (2) Alternatively, a soluble acidic salt is dissolved in deionized water to prepare a near-neutral salt solution, wherein the concentration of the near-neutral salt solution is 0.1-1 mol L -1 , adding a certain amount of sodium 2,6-naphthalene disulfonate to prepare a near-neutral electrolyte, wherein the pH range of the near-neutral electrolyte is 5-7;

[0010] (3) Alternatively, a soluble alkaline salt is dissolved in deionized water to prepare an alkaline salt solution, wherein the concentration of the alkaline salt solution is 1-10 mol L -1 , adding a certain amount of sodium 2,6-naphthalene disulfonate to prepare an alkaline electrolyte, wherein the pH range of the alkaline electrolyte is 13-14;

[0011] (4) Preparation of acidic / near-neutral full battery: zinc metal is used as the negative electrode, carbon material / manganese-based compound is used as the positive electrode material, and glass fiber is used as the separator. The acidic electrolyte prepared in step (1) or the near-neutral electrolyte prepared in step (2) is added dropwise to assemble into a button cell (CR2032 type) or a soft pack cell, and its zinc storage performance is tested;

[0012] (5) Preparation of alkaline full battery: zinc metal is used as the negative electrode, manganese-based / nickel-based compound is used as the positive electrode material, glass fiber is used as the separator, and the alkaline electrolyte prepared in step (3) is added dropwise to assemble into a button cell (CR2032 type) or a soft pack cell, and its zinc storage performance is tested.

[0013] Furthermore, the soluble acidic salts described in step (1) and step (2) include but are not limited to zinc sulfate, zinc nitrate, zinc trifluoromethanesulfonate, zinc acetate, zinc chloride, and zinc perchlorate; the soluble alkaline salts described in step (3) include but are not limited to potassium hydroxide and sodium hydroxide.

[0014] Furthermore, the concentration of the sodium 2,6-naphthalene disulfonate additive in the electrolyte is 1-100 mmol L -1 .

[0015] Furthermore, zinc metal includes but is not limited to zinc foil and zinc powder.

[0016] Furthermore, the manganese-based compound positive electrode material is prepared by the following method, and the method for preparing the manganese-based compound is an electrodeposition method: using lithium manganate leaching solution as a deposition solution, using three electrodes for deposition, wherein silver / silver chloride is a reference electrode, a platinum electrode is a working electrode, and a carbon cloth is a counter electrode, using an electrochemical time-transient test, setting the voltage to 1V, and the deposition time to 300s, manganese dioxide is deposited on the carbon cloth, and finally using a muffle furnace, setting 350°C to calcine for 2h to obtain a manganese dioxide composite positive electrode sheet, wherein the mass loading of the positive electrode material of the manganese-based compound active substance is 1.0-10.0 mg cm -2 .

[0017] Furthermore, the carbon material nickel-based positive electrode material is prepared by the following method: using commercially available carbon / nickel-containing active material, the mass ratio of carbon / nickel-containing active material: conductive agent: binder is 8:1:1, adding an appropriate amount of solvent to mix and prepare a slurry, coating the slurry on the current collector, and drying at 80°C for 10h to obtain a carbon material / nickel-based positive electrode sheet, wherein the mass loading of the carbon / nickel-containing active material positive electrode material is 1.0-10.0 mg cm -2 .

[0018] The application of the above-mentioned method for preparing the electrolyte of the zinc-based energy storage device of the present invention is characterized in that the method for assembling a button battery is as follows: zinc metal is used as the negative electrode, the positive electrode material prepared by the above-mentioned method for preparing the electrolyte of the zinc-based energy storage device is used as the positive electrode, glass fiber is used as the diaphragm, and 80 μL of the electrolyte prepared by the above-mentioned method for preparing the electrolyte of the zinc-based energy storage device is added dropwise to assemble into a button battery.

[0019] The application of the above-mentioned method for preparing the electrolyte of the zinc-based energy storage device of the present invention is characterized in that the method for assembling the soft-pack battery is as follows: the size of the aluminum-plastic film of the outer packaging body is 11 cm×11 cm, the single-piece area of ​​the zinc metal negative electrode is 9 cm×9 cm, the single-piece area of ​​the manganese-based / nickel-based compound positive electrode sheet is 8 cm×8 cm, and the single-piece area of ​​the glass fiber separator is 10 cm×10 cm. The negative electrode, the separator, and the positive electrode are stacked in sequence, and the electrolyte prepared by the above-mentioned method for preparing the electrolyte of the zinc-based energy storage device is introduced to assemble to obtain a soft-pack battery.

[0020] Specifically, the method for preparing an electrolyte suitable for acidic, near-neutral and alkaline zinc-based energy storage devices described in the present invention comprises the following steps:

[0021] (1) dissolving a soluble acidic salt in deionized water to prepare an acidic salt solution, wherein the concentration of the acidic salt solution is 2-5 mol L -1 , add sodium 2,6-naphthalene disulfonate to prepare an acidic electrolyte with a pH range of 1-4;

[0022] (2) Alternatively, a soluble acidic salt is dissolved in deionized water to prepare a near-neutral salt solution, wherein the concentration of the near-neutral salt solution is 0.1-1 mol L -1 , add sodium 2,6-naphthalene disulfonate to prepare a near-neutral electrolyte with a pH range of 5-7;

[0023] (3) Alternatively, a soluble alkaline salt is dissolved in deionized water to prepare an alkaline salt solution, wherein the concentration of the alkaline salt solution is 1-10 mol L -1 , add sodium 2,6-naphthalene disulfonate to prepare an alkaline electrolyte with a pH range of 13-14;

[0024] (4) Preparation of acidic / near-neutral full battery: With zinc metal as the negative electrode, carbon material / manganese-based compound as the positive electrode material, and glass fiber as the separator, the acidic electrolyte prepared in step (1) or the near-neutral electrolyte prepared in step (2) is added dropwise to assemble into a button cell (CR2032 type) or a soft-pack cell, and its zinc storage performance is tested.

[0025] (5) Preparation of alkaline full battery: zinc metal is used as the negative electrode, manganese-based / nickel-based compound is used as the positive electrode material, glass fiber is used as the separator, and the alkaline electrolyte prepared in step (3) is added dropwise to assemble into a button cell (CR2032 type) or a soft pack cell, and its zinc storage performance is tested.

[0026] The soluble acidic salts described in the above steps (1)-(2) include but are not limited to zinc sulfate, zinc nitrate, zinc trifluoromethanesulfonate, zinc acetate, zinc chloride, and zinc perchlorate; the soluble alkaline salts described in the above step (3) include but are not limited to potassium hydroxide and sodium hydroxide.

[0027] The optimal concentration of the sodium 2,6-naphthalene disulfonate additive in the above steps (1) to (3) is 1-100 mmol L -1 It can use the double-end capture function to regulate the concentration polarization at the interface, reconstruct the solvation process, accelerate the desolvation process, and inhibit dendrite growth; it uses chemical adsorption to build a molecular layer on the surface to isolate water and slow down side reactions.

[0028] The zinc metal used in the preparation of the zinc-based energy storage device in the above steps (4) and (5) includes but is not limited to zinc foil and zinc powder.

[0029] The method for preparing the manganese-based compound positive electrode material in the above step (4) is an electrodeposition method: using lithium manganate leaching solution as a deposition solution, using three electrodes for deposition, wherein silver / silver chloride is a reference electrode, a platinum electrode is a working electrode, and a carbon cloth is a counter electrode, using an electrochemical time-transient test, setting the voltage to 1V, and the deposition time to 300s, manganese dioxide is deposited on the carbon cloth. Finally, a muffle furnace is used, set to 350°C for calcination for 2h to obtain a manganese dioxide composite positive electrode sheet, wherein the mass loading of the positive electrode material containing the manganese active substance is 1.0 to 10.0 mg cm -2 .

[0030] The method for preparing the carbon material / nickel-based positive electrode material in the above steps (4) and (5) is as follows: using commercially available carbon / nickel-containing active material, the mass ratio of carbon / nickel-containing active material: conductive agent: binder is 8:1:1, adding an appropriate amount of solvent to mix and prepare a slurry, coating the slurry on a current collector, and drying at 80°C for 10 hours to obtain a carbon material / nickel-based positive electrode sheet, wherein the mass loading of the carbon / nickel-containing active material is 1.0 to 10.0 mg cm -2 .

[0031] The method for assembling button batteries in steps (4) and (5) above is as follows: zinc metal is used as the negative electrode, the electrode sheet prepared above is used as the positive electrode, glass fiber is used as the separator, and 80 μL of the aqueous electrolyte prepared by the above preparation method is added dropwise to assemble the button battery.

[0032] The method for assembling a soft-pack battery in the above steps (4) and (5) is as follows: the size of the aluminum-plastic film of the outer packaging body is 11 cm×11 cm, the single-piece area of ​​the zinc metal negative electrode is 9 cm×9 cm, the single-piece area of ​​the manganese-based / nickel-based compound positive electrode sheet is 8 cm×8 cm, and the single-piece area of ​​the glass fiber separator is 10 cm×10 cm. The negative electrode, the separator, and the positive electrode are stacked in sequence, and the aqueous electrolyte prepared by any preparation method described in the above steps (1)-(3) is introduced to assemble a soft-pack battery.

[0033] Compared with the existing technology, the present invention has the following specific advantages:

[0034] (1) Electrolyte additives are the most promising modification method to improve the performance of zinc-based energy storage devices. They are simple to operate and have obvious effects.

[0035] (2) As an additive, sodium 2,6-naphthalene disulfonate has low cost, high safety, is non-toxic and harmless, and has environmental and economic benefits.

[0036] (3) The present invention introduces sodium 2,6-naphthalene disulfonate additives into acidic, near-neutral and alkaline electrolytes to reconstruct the solvation structure of zinc ions, accelerate the desolvation process, and simultaneously construct an ordered and stable monolayer to protect the zinc negative electrode through chemical adsorption, thereby improving the electrochemical reversibility of zinc-based energy storage devices.

[0037] (4) The sodium 2,6-naphthalene disulfonate additive is effective and practical. The full battery assembled using a wide pH electrolyte containing sodium 2,6-naphthalene disulfonate has the advantages of long cycle life and stability. -1 Cycling 13000 times at current density, near neutral Zn||MnO2 full battery at 3Ag -1 Current density cycle 5000 times, alkaline Zn||Ni 0.8 Co 0.1 Mn 0.1 O2 full cell at 3Ag -1 The current density was cycled for 500 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a calculated diagram of the adsorption energy of water and sodium 2,6-naphthalene disulfonate on the Zn (002) crystal plane in the electrolyte obtained in Example 1.

[0039] Figure 2 This is a SEM image of the zinc negative electrode after the acidic electrolyte obtained in Example 1 is assembled into a battery and cycled.

[0040] Figure 3 This is an AFM image of the zinc negative electrode after the acidic electrolyte obtained in Example 1 is assembled into a battery and cycled.

[0041] Figure 4 The acid electrolyte obtained in Example 1 was assembled into a symmetrical battery at 4 mA cm -2 Cycling performance diagram at current density of .

[0042] Figure 5 The near-neutral electrolyte obtained in Example 1 was assembled into a symmetrical battery at 4 mA cm -2 Cycling performance diagram at current density of .

[0043] Figure 6 The alkaline electrolyte obtained in Example 1 was assembled into a symmetrical battery at 0.5 mA cm -2 Cycling performance diagram at current density of .

[0044] Figure 7 The Zn||MnO2 full battery assembled with the acidic electrolyte obtained in Example 1 is 5Ag -1 Cycling performance diagram at different current densities.

[0045] Figure 8 The Zn||MnO2 full battery assembled with the near-neutral electrolyte obtained in Example 1 at 3A g -1 Cycling performance diagram at different current densities.

[0046] Fig. 9 The alkaline electrolyte obtained in Example 1 is assembled into Zn||Ni 0.8 Co 0.1 Mn 0.1 O2 full battery at 3A g -1 Cycling performance diagram at different current densities.

[0047] Fig.10 The Zn||MnO2 soft-pack full battery assembled with the acidic electrolyte obtained in Example 1 is 0.1Ag -1 Cycling performance diagram at different current densities.

[0048] Fig.11 The Zn||MnO2 soft-pack full battery assembled with the acidic electrolyte obtained in Example 1 is used in series for charging a mobile phone. DETAILED DESCRIPTION

[0049] Example 1

[0050] Weigh a certain mass of zinc sulfate solid (2.904 g) and sodium 2,6-naphthalene disulfonate powder (2.5 mg), add 5 ml of deionized water, and ultrasonicate until transparent and clear to obtain an acidic electrolyte containing sodium 2,6-naphthalene disulfonate with a pH of 3.64; weigh a certain mass of zinc sulfate solid (0.436 g) and sodium 2,6-naphthalene disulfonate powder (2.5 mg), add 5 ml of deionized water, and ultrasonicate until transparent and clear to obtain a near-neutral electrolyte containing sodium 2,6-naphthalene disulfonate with a pH of 5.98; weigh a certain mass of potassium hydroxide solid (0.280 g) and sodium 2,6-naphthalene disulfonate powder (2.5 mg), add 5 ml of deionized water, and ultrasonicate until transparent and clear to obtain an alkaline electrolyte containing sodium 2,6-naphthalene disulfonate with a pH of 13.26;

[0051] Attached Figure 1 This is the calculated diagram of the adsorption energy of water and sodium 2,6-naphthalene disulfonate on the Zn (002) crystal plane. As can be seen from the figure, the adsorption energy of sodium 2,6-naphthalene disulfonate formed by dissolving sodium 2,6-naphthalene disulfonate in deionized water on Zn (002) (-6.71eV) is stronger than the adsorption energy of water on Zn (002) (-0.29eV). Therefore, sodium 2,6-naphthalene disulfonate is adsorbed on the surface of the zinc negative electrode before water to form a monolayer, isolating water from the electrode contact and improving the stability of the zinc negative electrode. Figure 2 This is a SEM image of the zinc negative electrode after the battery cycle was assembled with an acidic electrolyte. It can be seen from the figure that the electrolyte introduced with sodium 2,6-naphthalene disulfonate effectively protects the zinc negative electrode and inhibits dendrite growth and side reactions. Figure 3 The AFM image also shows that the zinc ions are uniformly deposited and the zinc negative electrode is flat without large protrusions. Therefore, using acidic, near-neutral and alkaline electrolytes containing sodium 2,6-naphthalene disulfonate, the zinc||zinc symmetric battery has a cycle life of 7200 hours ( Figure 4 ), 500 hours( Figure 5 ) and 220 hours ( Figure 6 In addition, a Zn||MnO2 full battery was assembled with a zinc metal sheet as the negative electrode, Whatman GF / A as the separator, and an acidic electrolyte containing sodium 2,6-naphthalene disulfonate at 5Ag -1 Cycle 13000 times at current density ( Figure 7 ), near-neutral electrolyte assembled Zn||MnO2 full battery in 3Ag -1 Current density cycle 5000 times ( Figure 8 ), alkaline electrolyte assembly Zn||Ni 0.8 Co 0.1 Mn 0.1 O2 full cell at 3Ag -1 Cycle 500 times at current density ( Fig. 9 ). In addition, a zinc sulfate electrolyte containing sodium 2,6-naphthalene disulfonate was used to organize a soft pack battery at 0.1Ag -1 After 100 cycles at the current density, the capacity is 190mAh ( Fig.10 ), connecting the soft pack batteries in series can charge the mobile phone ( Fig.11 ). These results demonstrate the applicability, effectiveness, and practicality of sodium 2,6-naphthalene disulfonate in acidic, near-neutral, and alkaline electrolytes.

[0052] Example 2

[0053] Weigh a certain mass of zinc chloride solid (1.36 g) and sodium 2,6-naphthalene disulfonate powder (25 mg), add 5 ml of deionized water, and ultrasonicate until transparent and clear to prepare an acidic electrolyte containing sodium 2,6-naphthalene disulfonate; measure a certain mass of concentrated sulfuric acid (270 μL) and dilute to 0.1 mol L -1 , introduce 2,6-sodium naphthalene disulfonate powder (25 mg), ultrasonicate until transparent and clear, to prepare a near-neutral electrolyte containing 2,6-sodium naphthalene disulfonate; weigh a certain mass of potassium hydroxide solid (0.840 g) and 2,6-sodium naphthalene disulfonate powder (25 mg), add 5 ml of deionized water, ultrasonicate until transparent and clear, to prepare an alkaline electrolyte containing 2,6-sodium naphthalene disulfonate;

[0054] The above-mentioned acidic, near-neutral and alkaline electrolytes are introduced respectively, the size of the aluminum-plastic film of the outer packaging body is 11cm×11cm, the single-piece area of ​​the zinc metal negative electrode is 9cm×9cm, the single-piece area of ​​the MnO2 positive electrode sheet is 8cm×8cm, and the single-piece area of ​​the glass fiber separator is 10cm×10cm. The negative electrode, separator, and positive electrode are stacked in sequence to assemble acidic, near-neutral and alkaline electrolyte soft-pack batteries respectively.

[0055] Example 3

[0056] Weigh a certain mass of zinc acetate solid (4.575 g) and sodium 2,6-naphthalene disulfonate powder (25 mg), add 5 ml of deionized water, and ultrasonicate until transparent and clear to obtain an acidic electrolyte containing sodium 2,6-naphthalene disulfonate; weigh a certain mass of zinc acetate (0.915 mg) and sodium 2,6-naphthalene disulfonate powder (25 mg), add 5 ml of deionized water, and ultrasonicate until transparent and clear to obtain a near-neutral electrolyte containing sodium 2,6-naphthalene disulfonate; weigh a certain mass of potassium hydroxide solid (0.840 g) and sodium 2,6-naphthalene disulfonate powder (25 mg), add 5 ml of deionized water, and ultrasonicate until transparent and clear to obtain an alkaline electrolyte containing sodium 2,6-naphthalene disulfonate;

[0057] The above-mentioned acidic, near-neutral and alkaline electrolytes were introduced respectively, and the respective Zn||Zn symmetric batteries and Zn||MnO2 full batteries were assembled to test their cycle performance.

[0058] Example 4

[0059] Weigh a certain mass of zinc trifluoromethanesulfonate (5.445 g) and sodium 2,6-naphthalene disulfonate powder (50 mg), add 5 ml of deionized water, and ultrasonicate until transparent and clear to obtain an acidic electrolyte containing sodium 2,6-naphthalene disulfonate; weigh a certain mass of potassium sulfate (0.435 mg) and sodium 2,6-naphthalene disulfonate powder (50 mg), add 5 ml of deionized water, and ultrasonicate until transparent and clear to obtain a near-neutral electrolyte containing sodium 2,6-naphthalene disulfonate; weigh a certain mass of sodium hydroxide solid (0.600 g) and sodium 2,6-naphthalene disulfonate powder (50 mg), add 5 ml of deionized water, and ultrasonicate until transparent and clear to obtain an alkaline electrolyte containing sodium 2,6-naphthalene disulfonate;

[0060] The above-mentioned acidic, near-neutral and alkaline electrolytes were introduced respectively, and Zn||Zn symmetric batteries and Zn||AC (activated carbon) capacitors were assembled respectively, and their cycle performances were tested.

[0061] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing an electrolyte suitable for acidic, near-neutral and alkaline zinc-based energy storage devices, the preparation steps of which are as follows: (1) Dissolving a soluble acidic salt in deionized water to prepare an acidic salt solution, wherein the concentration of the acidic salt solution is 2-5 mol L -1 , adding a certain amount of sodium 2,6-naphthalene disulfonate to prepare an acidic electrolyte, wherein the pH range of the acidic electrolyte is 1-4; (2) Alternatively, a soluble acidic salt is dissolved in deionized water to prepare a near-neutral salt solution, wherein the concentration of the near-neutral salt solution is 0.1-1 mol L -1 , adding a certain amount of sodium 2,6-naphthalene disulfonate to prepare a near-neutral electrolyte, wherein the pH range of the near-neutral electrolyte is 5-7; (3) Alternatively, a soluble alkaline salt is dissolved in deionized water to prepare an alkaline salt solution, wherein the concentration of the alkaline salt solution is 1-10 mol L -1 , adding a certain amount of sodium 2,6-naphthalene disulfonate to prepare an alkaline electrolyte, wherein the pH range of the alkaline electrolyte is 13-14; (4) Preparation of acidic / near-neutral full battery: zinc metal is used as the negative electrode, carbon material / manganese-based compound is used as the positive electrode material, and glass fiber is used as the separator. The acidic electrolyte prepared in step (1) or the near-neutral electrolyte prepared in step (2) is added dropwise to assemble a button cell (CR2032 type) or a soft pack cell, and its zinc storage performance is tested; (5) Preparation of alkaline full battery: Use zinc metal as the negative electrode, manganese-based / nickel-based compound as the positive electrode material, and glass fiber as the separator. Add the alkaline electrolyte prepared in step (3) to assemble into a button cell (CR2032 type) or a soft pack battery, and test its zinc storage performance.

2. The method for preparing an electrolyte for a zinc-based energy storage device according to claim 1, characterized in that: The soluble acidic salts described in step (1) and step (2) include but are not limited to zinc sulfate, zinc nitrate, zinc trifluoromethanesulfonate, zinc acetate, zinc chloride, and zinc perchlorate; the soluble alkaline salts described in step (3) include but are not limited to potassium hydroxide and sodium hydroxide.

3. The method for preparing an electrolyte for a zinc-based energy storage device according to claim 1, characterized in that: The concentration of sodium 2,6-naphthalene disulfonate additive in the electrolyte is 1-100 mmol L -1 .

4. The method for preparing an electrolyte for a zinc-based energy storage device according to claim 1, characterized in that: Zinc metal includes but is not limited to zinc foil and zinc powder.

5. The method for preparing an electrolyte for a zinc-based energy storage device according to claim 1, characterized in that: The manganese-based compound positive electrode material is prepared by the following method. The method for preparing the manganese-based compound is an electrodeposition method: lithium manganate leaching solution is used as a deposition solution, and three electrodes are used for deposition, wherein silver / silver chloride is used as a reference electrode, a platinum electrode is used as a working electrode, and a carbon cloth is used as a counter electrode. By using an electrochemical time-transient test, the voltage is set to 1 V, and the deposition time is set to 300 s, and manganese dioxide is deposited on the carbon cloth. Finally, a muffle furnace is used and calcined at 350° C. for 2 h to obtain a manganese dioxide composite positive electrode sheet, wherein the mass loading of the positive electrode material of the manganese-based compound active substance is 1.0-10.0 mg cm -2 .

6. The method for preparing an electrolyte for a zinc-based energy storage device according to claim 1, characterized in that: The carbon material nickel-based positive electrode material is prepared by the following method: using commercially available carbon / nickel-containing active material, the mass ratio of carbon / nickel-containing active material: conductive agent: binder is 8:1:1, adding an appropriate amount of solvent to mix and prepare a slurry, coating the slurry on the current collector, and drying at 80 ° C for 10 h to obtain a carbon material / nickel-based positive electrode sheet, wherein the mass loading of the carbon / nickel-containing active material positive electrode material is 1.0~10.0 mg cm -2 .

7. Application of the method for preparing an electrolyte for a zinc-based energy storage device according to any one of claims 1 to 6, characterized in that: The method for assembling a button battery is as follows: zinc metal is used as the negative electrode, the positive electrode material prepared by the method for preparing the electrolyte of a zinc-based energy storage device described in any one of claims 5-6 is used as the positive electrode, glass fiber is used as a separator, and 80 μL of the electrolyte prepared by the method for preparing the electrolyte of a zinc-based energy storage device described in any one of claims 1-3 is added dropwise to assemble into a button battery.

8. Application of the method for preparing an electrolyte for a zinc-based energy storage device according to any one of claims 1 to 6, characterized in that: The method for assembling a soft-pack battery is as follows: the size of the aluminum-plastic film of the outer packaging body is 11 cm×11 cm, the single-piece area of ​​the zinc metal negative electrode is 9 cm×9 cm, the single-piece area of ​​the manganese-based / nickel-based compound positive electrode sheet is 8 cm×8 cm, and the single-piece area of ​​the glass fiber separator is 10 cm×10 cm. The negative electrode, the separator, and the positive electrode are stacked in sequence, and the electrolyte prepared by the electrolyte preparation method for the zinc-based energy storage device according to any one of claims 1-3 is introduced to assemble a soft-pack battery.

Citation Information

Patent Citations

  • Electrolytic spray cleaning process for large metal workpiece

    CN102220625A

  • Preparation method and application of wide-pH electrolyte for high-performance zinc ion battery

    CN117559001A

  • Organic solid electrolytic capacitor and manufacturing method therefor

    JP1999121279A